The Existence of PT Jamsostek in Social Security Services For Workers with a Specific Time Work Agreement (PKWT) (Study at PT Jamsostek (Persero) Belawan Branch) - Jones Parapat (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2022)
The implementation of the social security program for workers based on a Specific Time Work Agreement (PKWT) in its implementation often does not work as expected which is able to provide protection and welfare / peace of mind for PKWT workers so that the authors are interested in raising this issue as a problem in the thesis. entitled "The Existence of PT Jamsostek (Persero) in Social Security Services for Workers with a Specific Time Work Agreement (PKWT)". This research is expected to be able to answer how the implementation of the labor social security program for PKWT workers, and find out what efforts can be made to ensure the protection of the Labor Social Security for PKWT workers, as well as the obstacles faced by PT Jamsostek (Persero) in providing Labor Social Security protection for PKWT workers. This research was conducted using library research and field research methods to obtain material as a reference in writing related to the problems of writing this thesis which in the end was able to provide benefits for various related parties in order to provide protection and welfare for workers. work especially for workers based on a Specific Time Work Agreement which in the end can play an active role in increasing economic growth for the welfare of the community and the future development of the nation.